Microwave Assisted Technology and its Role in Pharma Industry - Darekar, Avinash; Shahane, Akshata; Saudagar, Ravindra (Journal of Drug Delivery and Therapeutics, 2019)
Energy is the basic source required for carrying out work. Current paper describes a brief review of microwave technique, its use in pharmaceutical sciences. Microwave technique are being a traditional method for drying, synthesizing, preparing, heating, etc . They are also used during organic synthesis. Microwave can be used as cross heating barriers which arrive due to preliminary, insufficient heating of the product resulting in an inappropriate product. The microwave energy ranges from 300MHz to 300GHz which is sufficient enough for heating and drying of pharmaceuticals. Microwave techniques benefits one with time management, high percentage of yield, faster process, clear chemistry. Keywords: Microwave, drying, heating, application in pharmaceutical sciences